Behavior of lines from cotton primitive race stocks to attack of the boll weevil - Farias, Francisco José Correia; Lukefahr, Maurice James; Costa, Joaquim Nunes da; Freire, Elêusio Curvelo (Pesquisa Agropecuaria Brasileira, 1999)
The goal of the boll weevil (Anthonomus grandis Boheman) resistance program of Embrapa-Centro Nacional de Pesquisa de Algodão is to obtain cultivars that give 80% suppression when compared to commercial cultivars. The primitive cottons (Gossypium hirsutum L.) from Mexico and Central America have been known to show measurable levels of resistance to the boll weevil. In 1991 and 1992, the lines in BC1F5 and BC1F6 from Texas 277, Texas 326, Texas 1180, Texas 297, Texas 339, Texas 766 and Texas 1134 were evaluated to boll weevil resistance. The experiment was carried out at Campina Grande, PB, Brazil. The trial utilized was RCB with six replications. The plots were infested with newly emerged adults at the rate of 10,000 adults/ha. Six days after adults were released, the plots were sprayed with Cipermethrim. Infestation counts started three weeks after the Cipermethrim application and were made at weekly intervals. Five infestation counts were conducted by collecting 33 squares at random from each plot. The highest levels of resistance occurred in Texas 326-95-1, Texas 277-87-5, Texas 1180-99-2, Texas 297 and Texas 339 with 44.0, 41.2, 32.0, 40.4 and 36.4% of attack reduction, respectively, in relation to control CNPA 6H.